O balanço social como estratégia de fortalecimento das práticas de responsabilidade socioambiental - Nunes, Denise Xavier (2008)
Today's society are not any longer satisfied only with demanding from business the consecrated triangle that specifically deals with the quality, cost and due date. Conscientious of its place at the global world, it demands the involvement and the commitment of these Organizations with the social and environmental matters. In this context, it becomes necessary to invest on the preservation of nature, on its relation with society and the close relationship which involves direct and indirectly on this difficult task over the basics social contract. Answering these demands, accountaing science, facing the necessary requirements of this global market and in place of the model used until recently the decline corporative management model, that dealt only with the economic results, it created the Social Balance such as strategic instrument of corporative developments which allows the society to visualizes the results of its commitment with the future of the humanity. Those who do look to adapt itself to the new requirements of the global society, tend to fail. This research aims to analyze present whether companies in Brazil apply the concept of Social Responsibility in its activities, considering citizenship of serious and responsible form. Data available data by Petrobras, - Petróleo Brasileiro SA, Vale and Gerdau S.A, has been examed, describing information between its demonstratives and reports with the application from the considered ones for Institute ETHOS, investigating how much they care for or consider these questions and, later, comparing these results, making possible to conclude, the seriousness level that these companies practice these issues. The preference for the above-mentioned companies as object of research is for the position of prominence in the national and world-wide economic scenario; for its performance in the considered sectors of high level of degradation and consumption of natural resources; and for the high social impact generated by the organization in the place where it is introduced. The results indicate that companies start to visualize the environmental questions, verifying the information due to the absolute sums involved. However this concern has not reached the main idea of this social responsibility concept, addressing solely superficial strategic interests, promotion and auto-image.